"Low Echoic Area" around stent after bare and drug-coated stenting or stent graft placement for superficial femoral artery disease. (May 2021) - Soga, Yoshimitsu; Ando, Kenji
Restenosis after stent implantation in femoropopliteal lesions is still big issue. However, restenosis has been reduced by the recent new drug-eluting stent "Eluvia" (Boston Scientific, Marlborough, MA, USA). However, it was reported that "low echoic area (LEA)" finding around stent by ultrasound that they called "aneurysmal degeneration, " but no blood flow was identified outside the stent was confirmed after Eluvia implantation. In this report, we describe the similar findings that were observed after other types of stents (S.M.A.R.T. bare-nitinol stent (Cordis Corporation, Hialeah, FL, USA), Zilver PTX drug-coated stent (Cook Medical, Bloomington, IN, USA), and Viabahn stent graft (W. L. Gore & Associates, Newark, Delaware, USA)) for superficial femoral artery disease. These findings did not change to "aneurysmal change" during the follow-up.